The graduate tax when education is a signal - Ismail, Russayani; Myles, Gareth D. (Elsevier Ltd., 2015)
This paper investigates the effects of a graduate tax when the return to education is uncertain and wages are determined through equilibrium in a labor market with signalling.The consequence of uncertainty is that both ability and initial wealth matter for educational choice.Compared to a constrained first-best the market outcome with uncertainty and signalling results in an inefficiently high number of people entering higher education.Due to the positive wealth effect over-entry is proportionately greater for high-wealth individuals.The graduate tax reduces entry into education so enhances efficiency. However, it has undesirable distributional consequences: low-wealth individuals are deterred from entering education but high-wealth are encouraged.In this respect, the graduate tax has clear failings as a method of financing higher education.